RELATIONSHIP BETWEEN HbA1C AND eGFR IN DIABETES MELLITUS (DM) PATIENTS FOLLOWING PROLANIS AT ULTRA MEDICA TULUNGAGUNG CLINIC LABORATORY - taufik salis syaifuddin; Mutia Hariani Nurjanah; Nurul Chamidah Kumalasari; Wimbuh Tri widodo (Jurnal Biosains Pascasarjana, 2022)
Diabetes mellitus is a condition of abnormal blood glucose metabolism characterized by prolonged hyperglycemia and elevated HbA1c levels as a standard test for diabetes mellitus. HbA1c describes the level of sugar in the blood for the last 3 months. One of the complications of diabetes mellitus is kidney damage. The state of kidney function can be described from the GFR (Glomerular Filtration Rate) examination as a standard examination for abnormalities in kidney disease. The purpose of this study was to determine the relationship between HbA1c levels and eGFR values ​​in people with diabetes mellitus. The design of this study was a cross-sectional approach to 30 samples of DM patients who took Prolanis at the Ultra Medica Tulungagung Clinical Laboratory. The results showed that the average HbA1c level in all samples was 6.2% and the average eGFR value was 88.7 ml/min/1, 73m2. The Pearson correlation test obtained a ρ value = 0.000 so that it can be concluded that there is a relationship between HbA1c levels and eGFR values ​​in people with diabetes mellitus who take Prolanis at the Ultra Medica Clinical Laboratory Tulungagung.